PENGARUH KINERJA KEUANGAN TERHADAP PERTUMBUHAN LABA SEKTOR INDUSTRI DASAR KIMIA DI BEI - Pamungkas, Tri Hastuti; Nurlaela, Siti; Titisari, Kartika Hendra (Prosiding Seminar Nasional: Manajemen, Akuntansi, dan Perbankan; Vol 1 No 1 (2018): Prosiding Seminar Nasional dan Call for Papers Manajemen, Akuntansi, dan Perbankan 2018, 2018)
Current Ratio, Total Asset Turn Over Ratio, Gross Profit Margin, Debt To Assets Ratio to profit growth. The population in this research is Chemical Industry base company that exists in Indonesia stock exchange during period of 2012 - 2017 as many as 62 Basic Chemical Industry company. The sampling technique used purposive sampling method which was obtained from the sample of 13 companies during the observation year. Data analysis method used is multiple linear regression method. The test results show that the Quick Ratio, Current Ratio, Total Asset Turn Over Ratio, Debt To Assets Ratio does not affect the profit growth, while Profit Margin Margin, affect the profit growth. Based on the determination coefficient test (R2) obtained coefficient of determination with Adjusted R2 value of 0.181. These results indicate that 18.1% of the variable profit growth can be explained by quick ratio, current ratio, total asset trunover, gross profit margin, and debt to asset ratio. Meanwhile, 81.9% dependent variable of earnings management is influenced by other variables that do not exist in this research.